DISPARITIES DECISION RELATED TO INTERPRETATION OF ARTICLE 2 AND 3 CORRUPTION ERADICATION ACT - Agung Widodo (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
The discovery of the law by the judge in the court judgment is important. However, if these findings are based on a mistaken interpretation of the law, then such a step can not be regarded as legal discovery and it will have implications for the emergence of public disappointment. The results of analysis of 13 court verdict shows disparities legal interpretation both horizontally and vertically on Articles 2 and 3 of Law on Corruption Eradication. Among the legal interpretation of the most prominent of which are used judges is an interpretation of a restrictive, so that the element of "everyone" in Article 2 is interpreted as people who are not civil servants or state officials, while the element "any person" in Article 3 is interpreted as civil servants or state officials , The interpretation does not make sense because the resulting civil servants or state officials can not be charged under Article 2 (tort) and can only be charged under Section 3 (abuse of authority). Article 3 The minimum penalty is much lighter than a minimum sentence of Article 2, so that decisions are based on a restrictive interpretation of the implications for the injustice and legal uncertainty. In addition, in a systematic interpretation haldemikian contrary to criminal law umbrella because according to Article 52 of the Criminal Code, a threat to a crime in office plus one third. Keywords: discovery of law, corruption, abuse of authority.